2019
DOI: 10.1002/1873-3468.13715
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–liquid phase separation of the Golgi matrix protein GM130

Abstract: Golgins are an abundant class of peripheral membrane proteins of the Golgi. These very long (50–400 nm) rod‐like proteins initially capture cognate transport vesicles, thus enabling subsequent SNARE‐mediated membrane fusion. Here, we explore the hypothesis that in addition to serving as vesicle tethers, Golgins may also possess the capacity to phase separate and, thereby, contribute to the internal organization of the Golgi. GM130 is the most abundant Golgin at the cis Golgi. Remarkably, overexpressed GM130 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 40 publications
2
54
0
Order By: Relevance
“…Further, it has been shown that this relocation and assembly of the Golgi is dependent on the interaction of golgin160 with the minus‐end‐directed motor dynein, also implicating a specific golgin in the reassembly process [9]. We recently reported that the golgin GM130 phase separates into liquid‐like condensates both in vitro and in vivo [10], directly supporting the view that golgins can self‐assemble.…”
mentioning
confidence: 70%
“…Further, it has been shown that this relocation and assembly of the Golgi is dependent on the interaction of golgin160 with the minus‐end‐directed motor dynein, also implicating a specific golgin in the reassembly process [9]. We recently reported that the golgin GM130 phase separates into liquid‐like condensates both in vitro and in vivo [10], directly supporting the view that golgins can self‐assemble.…”
mentioning
confidence: 70%
“…Interactions with ELKS2 or other active zone proteins, some of which undergo phase separation as well ( Wu et al, 2019 ), may further account for the dynamic nature of vesicle clustering and vesicle progression toward release sites. Interestingly, even Golgins form liquid-phase condensates ( Rebane et al, 2020 ), and liquid-liquid-phase separation may be an organizational principle for vesicle tethering in the Golgi apparatus. Ultimately, an overarching and speculative model arises in which phase separation is a general mechanism through which vesicle tethering and traffic is organized throughout cells.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the effect of unlinking is not caused by GRASP55 or 65 depletion alone, arguing that the structural effect is indirect. Consistent with this notion, GM130 has recently been shown to self-organize by liquid-liquid phase separation (Rebane et al, 2020), which might be a mechanism to assemble and maintain the matrix by including other Golgi proteins into the condensate.…”
Section: Discussionmentioning
confidence: 72%